Crossidium geheebii (Pottiaceae, Bryophyta), a new record for the American continent - Cottet, Agustina C.; Messuti, María I. (Instituto de Ecología, A.C., 2022)
Background and Aims: Although the bryoflora of Argentina has been extensively studied, there are still environments to explore and taxa to record. The objective of this work was to report a new record, Crossidium geheebii, for the American continent.Methods: Specimens were collected in the Argentine Patagonia. Using an optical microscope, the morphology and anatomy of the leaves, stems and sporophytes were observed.Key results: A brief description, discussion, distribution map and illustration of the reported species are presented. Moreover, a key to identify the species of the genus Crossidium with distribution in America is included.Conclusions: Crossidium geheebii is reported for the first time for the American continent.